The application of neutron reflectometry and atomic force microscopy in the study of corrosion inhibitor films - John, Doug; Blom, A.; Bailey, Stuart; Nelson, A.; Schulz, J.; De Marco, Roland; Kinsella, Brian (Elsevier, 2006)
Corrosion inhibitor molecules function by adsorbing to a steel surface and thus prevent oxidation of the metal. The interfacial structures formed by a range of corrosion inhibitor molecules have been investigated by in situ measurements based on atomic force microscopy and neutron reflectometry. Inhibitors investigated include molecules cetyl pyridinium chloride (CPC), dodecyl pyridinium chloride (DPC), 1-hydroxyethyl-2-oleic imidazoline (OHEI) and cetyl dimethyl benzyl ammonium chloride (CDMBAC). This has shown that the inhibitor molecules adsorb onto a surface in micellar structures. Corrosion measurements confirmed that maximum inhibition efficiency coincides with the solution critical micelle concentration.